The detection of defects in tubes and plates using guided waves - Oaker, Bradley (Department of Mechanical Engineering, 2015)
Eddy current testing is the non-destructive test method of choice for the inspection of condenser tubes. However, unplanned shutdowns of power stations, due to unexpected condenser tube failures, still occur despite rigorous eddy current inspection programs. In addition to the improvement required in the reliability of inspections, there is also a need to shorten the duration of inspections.